The role of both mother job and the child's joining to the kindergarten in the improvement of decision making skill for a sample of the Third basic pupils - Jnad, Rawah; Jahjah, Reem (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research aims to detect the role of bothmother job and the child's joining to the kindergarten in the improvement of decision making skill for a sample of Third basic pupils in Lattakia city and to estimate the effect of the variables sort and achievement on this skill.Adescriptive method had been considered. For this purpose,a special test involving(30) statements within three headlines(determining the problem, generating alternatives, choosing the bestalternative),is designed.This testhad been carried out over arandom sample of (96)pupils. The results showed that the decision making skill exists in the tasted sample with alevel of medium. While no remarkable differenceshad been found according to the variable "sort",The study confirmed that motherjob and the child's joining to the kindergartenhave positive effects on decision making skill. The more thepupils' achievement increased, the moretheirdecision making skillincreased. Thesuggestions of the study:varying teaching methods especially those which contribute to the improvement of decision making skill.